1999
DOI: 10.1152/ajpgi.1999.276.2.g393
|View full text |Cite
|
Sign up to set email alerts
|

Slow waves in circular muscle of porcine ileum: structural and electrophysiological studies

Abstract: The structural and functional bases of pacemaking (slow waves) in porcine ileal circular muscle were studied. The myenteric plexus contained two, structurally distinct types of interstitial cells of Cajal (ICC) interconnected by gap junctions and connected by close contacts to muscle layers. At the deep muscular plexus, ICC were present, not regularly close to nerve axons or in gap junction contact with one another or outer circular muscle, which had many gap junctions. Slow waves (5.2 ± 2 mV amplitude and 4.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
23
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 46 publications
8
23
1
Order By: Relevance
“…Interestingly, slow waves were recorded in the circular muscle layer but it was not possible to make recordings of electrical activity from the longitudinal muscle layer. These results partially concur with the findings of Jiménez et al (1999) who found that slow wave amplitude varied with local membrane potential, suggesting that there may be a voltagedependent component in determining the amplitude of slow waves in the pig, presumably involving voltagesensitive ion channels. Although in this laboratory, Hudson et al (2001b) have recorded slow waves in the longitudinal muscle of equine ileum, to date, their presence has not yet been established in this layer in the pig.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Interestingly, slow waves were recorded in the circular muscle layer but it was not possible to make recordings of electrical activity from the longitudinal muscle layer. These results partially concur with the findings of Jiménez et al (1999) who found that slow wave amplitude varied with local membrane potential, suggesting that there may be a voltagedependent component in determining the amplitude of slow waves in the pig, presumably involving voltagesensitive ion channels. Although in this laboratory, Hudson et al (2001b) have recorded slow waves in the longitudinal muscle of equine ileum, to date, their presence has not yet been established in this layer in the pig.…”
Section: Discussionsupporting
confidence: 91%
“…The characteristics of these oscillations correlated well with the slow waves recorded in porcine ileum by other workers (Borderies et al 1997, Ferná ndez et al 1998, Jiménez et al 1999. The characteristics of these oscillations correlated well with the slow waves recorded in porcine ileum by other workers (Borderies et al 1997, Ferná ndez et al 1998, Jiménez et al 1999.…”
Section: Discussionsupporting
confidence: 84%
“…The reported length and time constants do not explain the nearly simultaneous onset of slow waves through the thickness of the circular muscle layers (Fig. 5B) (72,79,82).…”
Section: The Roles Of Icc In the Generation And Propagation Of Slow Wmentioning
confidence: 81%
“…The conductivity in the ICC-MP was assigned to be homogenous (isotropic) in all directions, in accordance with the intracellular recordings by Hirst et al (16),(18), and calcium imaging studies by Hening et al (21),(22), which have shown that ICC-MP propagates slow waves with equal velocity in all directions. Conduction in the ICC-MP network is slower than in the ICC-IM, despite the relative abundance of gap junctions in ICC-MP network (34). The specified ICC-MP conductivities were σ i = 50 mS mm −1 , σ e = 0.27 mS mm −1 .…”
Section: Circumferential Velocity Component Identificationmentioning
confidence: 99%